Challenges in providing spiritual care among healthcare workers: A qualitative study - Hairulisa@Mohd Hairi, Nur Alia; Wan Mamat, Wan Hasliza; Mohamad Shariff, Nurasikin; Jaafar, Siti Nur Illiani; Che Ahmad, Aminudin; Salah, Machouche (Kulliyyah of Medicine, International Islamic University Malaysia, 2025)
INTRODUCTION: Spiritual care has been identified as an integral component of holistic, culturally competent, and empathetic care. Although spiritual care offers tremendous benefits for patients, it can be challenging to implement. Despite its importance, there is a lack of literature in Malaysia on the challenges that healthcare workers encounter in providing spiritual care. Therefore, this study aimed to explore healthcare workers’ challenges in providing spiritual care to the hospitalised patients. MATERIALS AND METHODS: A qualitative study was conducted among healthcare workers at one hospital in Malaysia. A semi-structured interview was used to collect data from May 2023 until November 2023. All interviews were meticulously recorded, transcribed, and analysed using thematic analysis. RESULTS: Ten participants with diverse backgrounds willingly participated in the study. Analysis reveals a few challenges in providing spiritual care among healthcare workers such as time constraints, lack of knowledge, experience shortfalls, doubts about the efficacy of spiritual care, awareness deficiency among staff, and impact of patients’ conditions. CONCLUSION: Healthcare workers are unable to fulfil patients' spiritual care for a variety of reasons. These findings have important implications for healthcare settings, highlighting the need for ongoing awareness and training in spiritual care competencies for healthcare workers.